Who Can Speak? Rancière, Latour and the Question of Articulation - Iwona Janicka (Humanities, 2020)
In recent years, scholars in broadly considered posthumanities have attempted to reconceptualize politics in order to better account for the role of nonhuman entities in political processes. In this context, the article instantiates a dialogue between Jacques Rancière and Bruno Latour on one of the fundamental questions of politics, that is, the question of logos. Even though Latour and Rancière differ considerably in their theoretical and political orientations, each of them revisits the question of ‘who can speak?’ in order to examine the ways in which speechless entities gain a voice, thereby becoming intelligible as political entities. In this article, I confront Rancière’s reservations about nonhumans as political agents, showing how Latour offers pathways beyond Rancière’s apparent bias towards the human, a bias that is, I argue, fundamentally contradictory to the latter’s broader conceptualization of politics as aesthetics. I formulate a Latourian rebuttal of Rancière’s reservations and analyse the utility of Latour’s thought in overcoming Rancière’s limitations. Latour’s reorientation of logos towards the concept of ‘articulation’ makes it possible to evacuate, to some extent, the human exceptionalism from Rancière’s philosophy. Combining Latour with Rancière permits to fundamentally rearticulate the parameters of left-wing thinking about nonhumans.